Assessing the effects of drainage and forest structure on presence and absence of fledglings of boreal grouse - Ruottinen, Katri M.; Melin, Markus; Miettinen, Janne; Kervinen, Matti; Pakanen, Veli-Matti; Forsman, Jukka T.; Rytkönen, Seppo (Elsevier, 2024)
Anthropogenic factors threaten biodiversity of natural habitats globally, including boreal forest habitats of culturally important game species, such as grouse. Forestry and intense draining of wetlands have resulted in landscape fragmentation of the peatlands and the forests in terms of their structure (a mosaic of differently managed small stands), and the loss and alteration of natural grouse habitats, which impacts on fitness parameters are still partly unexamined. We used grouse brood location data from the Finnish wildlife triangle censuses from 2017 to 2020 to study how forest structure and drainage affect breeding success of four grouse species. We calculated environmental characteristics (forest and landscape structure, peatlands and their drainage status) around individual brood observations with different buffer sizes and used them to explain brood size variation and the probability of complete failure (female with no brood). While the most important buffer zones differed by species, brood sizes were generally linked to habitats that offer shelter and food. Black grouse brood size increased when the proportions of deciduous trees and xeric heath forests increased. Hazel grouse broods were largest in spruce-dominated mires and herb-rich forests. Willow grouse brood size decreased with increasing proportion of poorer barren heath forest habitat. Capercaillie brood size decreased as a function of drainage ditch length. In Capercaillie and Black grouse, females without broods were overrepresented (zero-inflation), and the zero excess was related to habitats that differed from those of brooded females. These results suggest that forest management methods and peatland drainage can have a negative effect on offspring production of boreal grouse species. Restoration of natural peatlands and less invasive management such continuous cover forestry should enhance environmental conditions for grouse.
Keywords: grouse; landscape; forest management; drainage; boreal forestry